Study of Graft Copolymerization of Acrylic Acid Onto Nata De Coco and its Application as Microfiltration Membrane - T Puspitasari; CL Radiman (Atom Indonesia, 2006)
Chemical and physical modifications of membrane can be carried out by radiation induced graft copolymerization. The aim of this research is to prepare graft copolymers of acrylic acid onto nata de coco (NDC-g-AAc) by radiation and to study the performance of grafted copolymer as microfiltration membrane. Using a total dose of 30 kGy, the highest degree of grafting obtained were 209% and 142% for r (weight ratio of monomers to nata de coco) equal to 61.3 and 35.7 respectively. The increasing degree of grafting resulted in decreasing flux due to high hydrogen bonding between grafted acrylic groups and water. It was found that the degree of swelling of NDC-g-AAc membrane with r = 35.7 was higher than that of r = 63.1. The changes of chemical structure of membrane were characterized by FTIR spectroscopy which showed a new band at 1720 cm-1 attributed to the carbonyl group of acrylic acid